Book ordering and management system - Teh, Kok Yang (2014)
Web technology is a potential technology that evolved over the years to provide different convenient to people. In this project, a web-based book ordering and system is developed for Petakom. Currently, FSKKP students in UMP are ordering book from Petakom manually. This method is time consuming and inconvenient for them. Besides that, lecturers in UMP are ordering their book for class through Faculty. This method is slow and inconvenient. On the other hand, Petakom is managing the book ordering manually. Hence, this system is developed to provide a solution for lecturer and student to order the personal and book for class from Petakom. At the same time, this system allows Petakom to manage the book ordering. Through this system, student and lecturer can order the books conveniently. Petakom also can manage the book ordering in more systematically and easily. Futhermore, this system also provides the functions of view news, post news, sms, check ordering records and view book ordering statistic.